Surfactant-free synthesis of anisotropic gold nanostructures: can dicarboxylic acids alone act as shape directing agents? - Kumar, D. V. Ravi; Kumavat, S. R.; Chamundeswari, V. N.; Patra, Partha Pratim; Kulkarni, A. A.; Bhagavatula L. V. Prasad (RSC Advances, 2013)
The present study describes the synthesis of gold nanostructures using different dicarboxylic (viz. oxalic, malonic, succinic, glutaric and adipic) acids as reducing agents in the absence of any other additives or surfactants. Various anisotropic structures such as kites, tadpoles, triangular/hexagonal plates, and twinned particles were seen to evolve depending on the molar ratio of dicarboxylic acid to HAuCl4 used. It was also demonstrated that gold nanostructure formation is hampered as the chain length/distance between two carboxylic acid groups increases. Among the various structures obtained the kite like structures displayed the largest surface enhanced Raman enhancement factors.